Analisis Tingkat Kepuasan Pengguna Aplikasi Satu Sehat Pada UPTD Puskesmas Cempaka - Tata Sutabri; Deska Novita Sari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Lamappapoleonro, 2025)
This study analyses the user satisfaction level of the Satu Sehat application, a digital platform developed by the Indonesian government to support integrated health services for the community. The research uses a descriptive method with a quantitative approach, utilising the End User Computing Satisfaction (EUCS) model from Doll and Torkzadeh (1988) to evaluate employee satisfaction. Data was collected through a survey to measure the perception and satisfaction of users of the SISDMK application. From a population of 80 respondents, 67 samples were sampled using the Slovin formula. Data analysis involved validity and reliability tests. The results showed that in the Content (X1) variable, six statements were valid with a validity value above rtable 0.2404 and an alpha coefficient of 0.802. Accuracy (X2) variable was valid with an alpha of 0.811. Format (X3) has a reliability of 0.796, Ease of Use (X4) is valid with an alpha of 0.873, and Timeliness (X5) is valid with a reliability of 0.852. All variables are declared valid and reliable.